Investigating Perceived Barriers to the Use of Open Educational Resources in Higher Education in Tanzania - Mtebe, Joel S.; Raisamo, Roope (International Review of Research in Open and Distributed Learning, 2014)
The past few years have seen increasingly rapid development and use of open educational resources (OER) in higher education institutions (HEIs) in developing countries. These resources are believed to be able to widen access, reduce the costs, and improve the quality of education. However, there exist several challenges that hinder the adoption and use of these resources. The majority of challenges mentioned in the literature do not have empirically grounded evidence and they assume Sub-Saharan countries face similar challenges. Nonetheless, despite commonalities that exist amongst these countries, there also exists considerable diversity, and they face different challenges. Accordingly, this study investigated the perceived barriers to the use of OER in 11 HEIs in Tanzania. The empirical data was generated through semi-structured interviews with a random sample of 92 instructors as well as a review of important documents. Findings revealed that lack of access to computers and the Internet, low Internet bandwidth, absence of policies, and lack of skills to create and/or use OER are the main barriers to the use of OER in HEIs in Tanzania. Contrary to findings elsewhere in Africa, the study revealed that lack of trust in others’ resources, lack of interest in creating and/or using OER, and lack of time to find suitable materials were not considered to be barriers. These findings provide a new understanding of the barriers to the use of OER in HEIs and should therefore assist those who are involved in OER implementation to find mitigating strategies that will maximize their usage.